Palatal click allophony in Mangetti Dune !Xung: Implications for sound change. (23rd August 2017) - Miller, Amanda L.
Abstract : Click consonants are well known for lacking allophonic variation. This lack of variation has been attributed to the existence of articulatory constraints on the coronal constrictions that are imposed by the existence of a second dorsal constriction. The current study investigates temporal acoustic differences among the four contrastive coronal click types in the /i / and /u / contexts in Mangetti Dune !Xung. Clicks have been described as being either non-affricated or affricated. However, when vowel context is taken into consideration, the typology is more complex. The alveolar click is non-affricated in both vowel contexts. The dental and lateral clicks are fricated in both contexts. The palatal click in the /i / context has two clear anterior and posterior transients, followed by palatal frication, while in the /u / context it is non-affricated. Results are consistent with an analysis of the palatal click in the /i / context as involving allophonic secondary palatalization. There are trading relations between the duration of the click burst, frication noise and aspiration noise phases. Results have implications for understanding the synchronic and diachronic phonology of click consonants.